SINTESIS KALKON PIRIDIN DAN TURUNANNYA DARI ASETILPIRIDIN DAN INDOL-3-KARBALDEHID SERTA UJI AKTIVITASNYA SEBAGAI ANTIOKSIDAN - Juwita Oktavani; Hilwan Yuda Teruna; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
In this research, chalcones of acetylpyridine derivatives were synthesized using stirrer method with a base catalyst (NaOH) at room temperature. The compound produced from the synthesis was (E)-3-(1H-indole-3-yl)-1-(pyridine-3-yl)prop-2-en-1-one (1). The synthesized compound was characterized using UV, IR, NMR and Mass Spectroscopy. Its antioxidant activity was tested using DPPH method which compound (1) showed mild antioxidant activity proved by IC 50 > 250 µg/mL.